Popular movements in autocracies: religion, repression, and indigenous collective action in Mexico - Trejo, Guillermo ca. 20./21. Jh. (Cambridge studies in comparative politics, 2012)
A new explanation of the rise, development and demise of social movements and cycles of protest in autocracies.